Aging and glycation promote erythrocyte phagocytosis by human endothelial cells: Potential impact in atherothrombosis under diabetic conditions. (December 2019) - Catan, Aurélie; Turpin, Chloé; Diotel, Nicolas; Patche, Jessica; Guerin-Dubourg, Alexis; Debussche, Xavier; Bourdon, Emmanuel; Ah-You, Nathalie; Le Moullec, Nathalie; Besnard, Mathieu; Veerapen, Reuben; Rondeau, Philippe; et al.
Abstract: Background and aims: Atherothrombotic plaques of type 2 diabetic (T2D) patients are characterized by an increased neovascularization and intraplaque hemorrhage. The clearance of erythrocytes may be carried out by vascular cells. We explored the potential of human endothelial cells to bind and phagocyte in vitro aged and/or glycated erythrocytes as well as erythrocytes obtained from diabetic patients. Methods: Fresh, aged and glycated-aged erythrocytes from healthy volunteers and T2D patients were tested for their binding and phagocytosis capacity as well as the potential functional consequences on endothelial cells (viability, proliferation and wound healing capacity). Immunohistochemistry was also performed in human carotid atherothrombotic samples (from patients with or without T2D). Results: Aging and glycation of erythrocytes induced phosphatidylserine (PS) exposure and oxidative stress leading to enhanced endothelial cell binding and engulfment. Phagocytosis by endothelial cells was more pronounced with aged and glycated erythrocytes than with fresh ones. Phagocytosis was enhanced with T2D versus healthy erythrocytes. Furthermore, endothelial wound healing potential was significantly blunted after exposure to glycated-aged versus fresh erythrocytes. Finally, we show that interactions between erythrocytes and endothelial cells and their potential phagocytosis may occur in vivo, in atherothrombotic conditions, in neovessels and in the luminal endothelial lining. Conclusions: Endothelial cells may play an important role in erythrocyte clearance in an atherothrombotic environment. Under diabetic conditions, erythrocyte glycation favors their engulfment by endothelial cells and may participate in endothelial dysfunction, thereby promoting vulnerable atherothrombotic plaques to rupture. Graphical abstract: Image 1 Highlights: The clearance of erythrocytes may be carried out by vascular cells in atherosclerotic conditions. Phagocytosis by endothelial cells is more pronounced with aged and glycated erythrocytes. Endothelial phagocytosis is enhanced with T2D erythrocytes. Interactions between erythrocytes and endothelial cells occur in vivo, in atherothrombotic/diabetic conditions.